Digital Transformation and Organizational Performance : Digital transformation and good governance - El Bettioui, Rachid (2023)
Good governance in the age of digital transformation is a strong sign of a good business climate for a multitude of economic and social players. This signal, which is the prelude to a business-friendly environment, consolidates trust between the different economic partners and encourages practices within organizations. Good governance thus favours the conditions for creating value for all the organization's partners. As part of its commitment to good governance under the new development model that came into force in 2021, Morocco has launched a series of reforms. In this regard, digitalization is the focal point of all the reforms undertaken and is intended to be the catalyst for structural progress in terms of simplification and quality of service for users, as well as in terms of the performance of public and private entities.